Survey of Ankle Coordination and Driving Ability of Students of SMK Negeri 4 Makassar - Achmad Karim; Muhammad Hasbillah; Herman Herman; Ikadarny Ikadarny (Universitas Majalengka, 2023)
This research is a type of descriptive research that uses a